Identificação das zonas de conflito entre onças-pintadas e a atividade pecuária no Brasil - Assis, Jasmine de Resende (2020)
The conflict with humans has been one of the main threats to wild carnivores, driven by the predation of cattle, which happens due to the destruction of habitat for the establishment of pasture areas, reduction of the base of natural prey, bad techniques of cattle management and by opportunistic behavior or learned by the predator. Based on this, in this dissertation, we explored the conflict between ranchers and jaguars in scientific works and identified the main environmental and anthropogenic predictors influencing the risk of cattle predation by jaguars in Brazil, with this study consisting of two chapters. The first chapter is a systematic review carried out with all the scientific work on the conflict between ranchers and jaguars from 1990 to 2018. We noticed the existence of some common themes in the studies, such as: predation of cattle; environmental and anthropic predictors influencing livestock predation; retaliatory hunting; human perception about the conflict and the jaguar; mitigating recommendations; management applied on farms and evaluated recommendations. It was identified: the need for further studies for the Cerrado and Caatinga, the evaluation of proposed mitigation methods and the application of better livestock management techniques. In the second chapter, we evaluate the importance of environmental and anthropogenic predictors in the predation of cattle by jaguars and map the risk of predation in Brazil. The best GLM model generated (AIC = 563.32) was represented by the variables environmental suitability for the species, herd density, distance from hydrography and number of rural properties, with this order of explanatory power for the risk of predation. Low environmental suitability combined with anthropogenic predictors such as low herd density and numerous rural properties, represented the most apt scenario for the predation of cattle by jaguars, similar to what happens in the Cerrado, Atlantic Forest and in the arc of deforestation in the Amazon.